Development of Smart Physics Student Magazine (SPSM)-Based Teaching Materials to Enhance Students' Scientific Literacy - Annisa Hafizoh; Lovy Herayanti; Saiful Prayogi (Indonesian Journal of STEM Education, 2024)
This research and development aimed to produce physics teaching materials based on Smart Physics Student Magazine (SPSM) and examine its effectiveness in improving scientific literacy among 10th-grade high school students in the second semester. The 4D development model (Define, Design, Develop, Disseminate) was employed, but this study only covered the first three stages. The subjects were 26 students from SMA Negeri 1 Kediri. Validation results showed that the SPSM-based teaching materials were deemed feasible by two validators with 76% and 79% percentages. The implementation of these materials also proved effective in improving students' scientific literacy, as indicated by positive responses from 89% of students with an average score of 93. Therefore, it is concluded that SPSM-based teaching materials are feasible and effective for use in teaching physics to 10th-grade high school students in the second semester.